Prosthodontic Rehabilitation Using Pterygoid Implant (Journal of Pharmaceutical Negative Results, 2022)
Background: Loss of teeth in the maxilla, specifically in the posterior segments, may complicate implant placement related toenlargement of the maxillary sinus through a combination of crestal resorption and pneumatization of the sinus, both natural occurrences. The posterior maxilla poses some challenges for the surgeon with limitations to implant placement. Those include low bone quality and quantity, pneumatization of the maxillary sinus and poor accessibility to the area. Low bone density at possible implant sites reduces implant success related to impairment of the primary stability of the implants.Aim: This systematic review describes various implant treatment options for posterior maxillary rehabilitation. It highlights the use of pterygoid implants as a graft less solution with its anatomy, technique of placement, and advantages.Results: Pterygoid implants allow restoration of the resorbed posterior maxilla in less time by avoiding the healing period required when osseous grafting would be required to place implants in the deficient ridge below the enlarged sinus.Conclusion: Pterygoid implants should be considered when inadequate bone is present in the posterior maxilla as an alternative to osseous augmentation to permit implant placement.Pterygoid implants have high success rates, less bone loss, and good acceptance by patients thus being an excellent alternative to treat patients with severely atrophic maxilla.